ATRIAL FIBRILLATION AND RENAL DYSFUNCTION: CURRENT STATE OF THE PROBLEM AND THE PROSPECTS OF FURTHER STUDY - K. V. Protasov; V. Z. Dorzhieva; E. A. Petuhova (Российский кардиологический журнал)
The review of literature is devoted to interrelations between atrial fibrillation (AF) and kidney function. The focus is on the most probable mechanisms of renal dysfunction in patients with atrial fibrillation such as fibrosis, inflammation, neurohormonal activation. The impact of central and renal hemodynamics disorders on chronic kidney disease development in atrial fibrillation patients is under consideration. The problem of atrial fibrillation in end-stage renal disease patients also gets the authors’ attention. We identified unresolved issues and the prospects for their further research.